Pentingnya Pemahaman Sosial Psikologis dalam Pembinaan Anak Panti Asuhan Sebuah Studi Kasus di Panti Asuhan Kristen Eunike Semarang - Greta Vidya Paramita (Humaniora, 2011)
This study aims to discuss the importance of social psychological understanding of coaching children in the orphanage. Coaching is the business, action, and carried out activities in an efficient and effective way to obtain a better result. Research conducted on 19 subjects in Eunice Christian Orphanage located in the city of Semarang. The research method used in this study is a qualitative method, namely through psychological examinations using diagnostic tool Draw A Man (DAM), Baum, and descriptions of themselves in writing. From the results of this study concluded that each foster child has the distinction that needs to be recognized by the head of the orphanage and the caregivers. Psychological understanding of social conditions necessary for development of each child which can be done right on target.